Rare bird documentation form for Lesser Black-backed Gull at Lock and Dam 15, 1995 - Kent, Thomas H. (Thomas Hugh), 1934-et al (1995)
Rare bird documentation form for a Lesser Black-backed Gull at Lock and Dam 15 in Scott County, IA on February 4, 1995. Epson - sheet feed